Impact of plaque and luminal morphology in balloon angioplasty of the femoropopliteal artery: an intravascular ultrasound analysis - Zou, Yuchi; Tong, Qiang; Wang, Xuehu; Jiang, Chuli; Dai, Yuanbin; Zhao, Yu; Cheng, Jun (Frontiers in Cardiovascular Medicine, 2023)
Objective: To assess the effect of plaque and luminal morphologies in balloon angioplasty of femoropopliteal lesions using intravascular ultrasound (IVUS). Methods: This retrospective, observational study analyzed 836 cross-sectional images, analyzed with IVUS, from 35 femoropopliteal arteries of patients who underwent endovascular treatment between September 2020 and February 2022. Pre- and post-balloon angioplasty images were matched per 5 mm. Post-balloon angioplasty images were grouped into successful (n=345) and unsuccessful (n=491) groups. Plaque and luminal morphologies (such as severity of calcification, vascular remodeling, and plaque eccentricity) were extracted before the balloon angioplasty procedure to identify the predictors of unsuccessful balloon angioplasty. Additionally, 103 images with severe dissection were analyzed using IVUS and angiography. Results: In univariate analyses, the predictive factors for unsuccessful balloon angioplasty were vascular remodeling (p<.001), plaque burden (p<.001), lumen eccentricity (p<.001), and balloon/vessel ratio (p=.01). Predictive factors for severe dissections were the guidewire route (p<.001) and balloon/vessel ratio (p=.04). In multivariate analysis, the predictive factors for unsuccessful balloon angioplasty included lumen eccentricity (odds ratio [OR] 3.99, 95% confidence interval [CI] 1.28 to 12.68, p=.02) and plaque burden (OR 1.03, 95% CI, 1.02 to 1.04; p<.001). For severe dissections, the independent risk factor was eccentricity and guidewire route (OR 2.10, 95 % CI 1.22 to 3.65, p=.01). Conclusion: High plaque burden and luminal eccentricity were risk factors for failed femoropopliteal artery balloon angioplasty. Additionally, the eccentric guidewire route predicted severe dissection.